Associating Parental to Child Psychological Symptoms: Investigating a Transactional Model of Development. (September 2013) - Fanti, Kostas A.; Panayiotou, Georgia; Fanti, Savvas
The current study investigated the longitudinal transactional association among paternal and maternal depressive symptoms and child internalizing and externalizing difficulties. Data were collected on preschool- to adolescent-age youth via a total of six assessments. The sample (National Institute of Child Health and Human Development [NICHD] Study of Early Child Care) consisted of 1, 098 biological mothers and 770 biological fathers. The findings suggest that boys were at lower risk for exhibiting internalizing problems across time and girls were less likely to exhibit externalizing problems. Compared with fathers, mothers reported higher levels of depressive symptoms. The Autoregressive Latent Trajectory models provided evidence for parental and child effects across time, which emphasizes the dynamic association among parental and child psychological symptoms. Differences in the timing of effects were also identified. Transactional associations among maternal and paternal depressive symptoms and child problem behaviors and emotions were identified during the transition from toddlerhood to school age and during adolescence. Finally, gender differences were evident in the transactional associations between parental and child psychological symptoms.